The relationship between patterns of benthic fauna and zooplankton in the Chukchi Sea and physical forcing - Pisareva, Maria; Pickart, Robert S.; Iken, Katrin; Ershova, Elizaveta; Grebmeier, Jacqueline M.; Cooper, Lee W.; Bluhm, Bodil; Nobre, Carolina; Hopcroft, Russell R.; Hu, Haoguo; Wang, Jia; Ashjian, Carin; et al. (Oceanography, 2015)
Published version also available at http://dx.doi.org/10.5670/oceanog.2015.58 Using data from a number of summer surveys of the Chukchi Sea over the past decade, we investigate aspects in which the benthic fauna, sediment structure, and zooplankton there are related to circulation patterns and shelf hydrographic conditions. A flow speed map is constructed that reveals the major pathways on the shelf. Regions of enhanced flow speed are dictated by lateral constrictions—in particular, Bering Strait and Barrow and Herald Canyons—and by sloping topography near coastlines. For the most part, benthic epifaunal and macrofaunal suspension feeders are found in high flow regimes, while deposit feeders are located in regions of weaker flow. The major exceptions are in Bering Strait, where benthic sampling was underrepresented, and in Herald Canyon where the pattern is inexplicably reversed. Sediment grain size is also largely consistent with variations in flow speed on the shelf. Data from three biophysical surveys of the Chukchi Sea, carried out as part of the Russian-American Long-term Census of the Arctic program, reveal close relationships between the water masses and the zooplankton communities on the shelf. Variations in atmospheric forcing, particularly wind, during the three sampling periods caused significant changes in the lateral and vertical distributions of the summer and winter water masses. These water mass changes, in turn, were reflected in the amounts and species of zooplankton observed throughout the shelf in each survey. Our study highlights the close relationship between physical drivers (wind forcing, water masses, circulation, and sediment type) in the Chukchi Sea and the biological signals in the benthos and the plankton on a variety of time scales.